Sensores baseados em nanotubos de carbono e grafeno na detecção de contaminantes em alimentos - Aguilar, Sofia Lasso Morales (Universidade Federal de São Carlos, 2025)
This final course project presents a literature review on graphene-based and carbon nanotubes (CNTs) sensors applied to the detection of contaminants in food, focusing on studies published between 2021 and 2025. The research was structured based on systematic screening of the Scopus, Web of Science, PubMed, ScienceDirect, and RSC Publishing platforms, among other academic databases. In this screening phase, titles and abstracts were considered as initial selection criteria. The searches on these research platforms included only articles with a direct approach to the use of these nanomaterials in the construction of sensors for food safety analysis. The methodology adopted is qualitative in nature, with a literature review developed as a research method. This study sought to identify relevant works on the subject, highlighting the characteristics of these nanomaterials, namely: morphology, properties, and synthesis methods, as well as their uses in sensors applied to food quality control. The research results point to a significant growth in studies involving graphene and CNTs in sensors due to the exceptional physicochemical properties of these materials, such as high electrical conductivity, large surface area, ease of functionalization and high molecular sensitivity. The studies reviewed show a strong trend towards integrating these sensors with technologies focused on artificial intelligence, machine learning, and the Internet of Things (IoT), from the perspective of real-time applications. However, analyses of these studies reveal challenges such as production costs and, furthermore, persisting challenges include material standardization, stability in complex food matrices, production costs, and validation for regulatory use. It is concluded that the combination of graphene and CNTs in sensors represents a suitable technology for monitoring food quality and safety.
Carbon nanotube- and graphene-based sensors for the detection of contaminants in food
Keywords: Sensores com grafeno; Sensores com nanotubos de carbono; Segurança do alimento; Graphene sensors; Carbon nanotube sensors; Food safety; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ELETROANALITICA; 3. Saúde e Bem-Estar; 6. Água Potável e Saneamento